Tuning the orbital ordering in La0.7Sr0.3MnO3 thin films in all-oxide hybrids. (March 2015) - Doğanay, H.; Krug, I. P.; Schubert, J.; Cramm, S.; Gottlob, D. M.; Nickel, F.; Schneider, C. M.
Abstract This work presents a systematic characterization including x-ray diffractometry, SQUID magnetometry and x-ray absorption spectroscopy on all-oxide ferromagnetic/ferroelectric heterosystem BaTiO3/La0.7Sr0.3MnO3/SrTiO3(001) fabricated by pulsed-laser deposition. The key aspect of this study is to provide accurate information about differences in electronic and structural properties in LSMO thin films as a function of the oxygen pressure during BTO growth. X-ray absorption spectroscopy experiments at the Mn L3, 2 edge have revealed the conservation of <?CDATA $\mathrm{Mn}^{3+}/\mathrm{Mn}^{4+}$ ?> <inline-graphic xlink:href="ark:/27927/pgjjmxv7ff" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> mixed valency configuration of the LSMO films near the interface while tuning the oxygen pressure of overlayer BTO growth. The existing <?CDATA $\mathrm{Mn}^{3+}$ ?> <inline-graphic xlink:href="ark:/27927/pgjjmxv2f1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> ions favor an in-plane eg orbital ordering, reducing the in-plane strain and promoting room temperature ferromagntism in the LSMO film. Furthermore, diffraction experiments showed that the out-of plane lattice parameter of BTO reduces with increasing oxygen pressure consistent with the x-ray linear dichrosim at Ti edge showing less tetragonal symmetry, although the chemical environment of the Ti ions was not changed notably. We demonstrated a way to control magnetic properties and orbital ordering in LSMO thin films while optimizing the ferroelectric properties of BTO overlayer films, which are promising results in terms of magnetoelectric applications using functional heterosystems.